The individual factors influence knowledge sharing behavior toward job performance in Kota Samarahan public higher learning institutions - Ho Yee, Ting (Universiti Malaysia Sarawak, 2019)
This research aimed to explore the individual factors on knowledge sharing behaviour towards job performance among academic staff and the research model is building on Social Exchange Theory. Four individual factors have been used in examining the knowledge sharing behaviour of academic staff which include knowledge self-efficacy, altruism, trust, and expectation. While this research also investigated the relationship between knowledge sharing behaviour and job performance. In such, five hypotheses in total were formulated and follow by experimented among academic staff of public higher learning institutions in Kota Samarahan. Data were collected from 161 academic staff through the survey questionnaire with five-point Likert scale. Software SPSS version 20.0 was used to analyse the collected data and the results shown that knowledge self-efficacy, altruism, trust, and expectation positively influence the knowledge sharing behaviour. Furthermore, knowledge sharing behaviour shown positive relationship on job performance. Next, altruism was the most important individual factor in affect the behaviour of knowledge sharing among academic staff.